Charge Carrier Mobility in Organic Mixed Ionic–Electronic Conductors by the Electrolyte‐Gated van der Pauw Method. (2nd August 2021) - Bonafè, Filippo; Decataldo, Francesco; Fraboni, Beatrice; Cramer, Tobias
Abstract: Organic mixed ionic–electronic conductors (OMIECs) combine electronic semiconductor functionality with ionic conductivity, biocompatibility, and electrochemical stability in water and are currently investigated as the active material in devices for bioelectronics, neuromorphic computing, as well as energy conversion and storage. Operation speed of such devices depends on fast electronic transport in OMIECs. However, due to contact resistance problems, reliable measurements of electronic mobility are difficult to achieve in this class of materials. To address the problem, the electrolyte‐gated van der Pauw (EgVDP) method is introduced for the simple and accurate determination of the electrical characteristics of OMIEC thin films, independent of contact effects. The technique is applied to the most widespread OMIEC blend, poly(3, 4‐ethylenedioxythiophene) doped with poly(styrenesulfonic acid) (PEDOT:PSS). By comparing with organic electrochemical transistor (OECT) measurements, it is found that gate voltage dependent contact resistance effects lead to systematic errors in OECT based transport characterization. These observations confirm that a contact‐independent technique is crucial for the proper characterization of OMIECs, and the EgVDP method reveals to be a simple, elegant, but effective technique for this scope. Abstract : A simple and accurate four‐point probe (FPP) characterization technique is introduced for the analysis of the transport properties of organic mixed ionic–electronic conductors. This technique is applied to microstructured poly(3, 4‐ethylenedioxythiophene) doped with poly(styrenesulfonic acid) (PEDOT:PSS) thin‐film devices for the extraction of the charge carrier mobility and the threshold voltage of the blend, independent of contact resistance effects.